2017
DOI: 10.1002/path.4940
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic necrotizing factor 1 promotes prostate cancer progression through activating the Cdc42–PAK1 axis

Abstract: Uropathogenic Escherichia coli (UPEC) is the leading cause of urinary tract infections and plays a role in prostatic carcinogenesis and prostate cancer (PCa) progression. However, the mechanisms through which UPEC promotes PCa development and progression are unclear. Cytotoxic necrotizing factor 1 (CNF1) is one of the most important UPEC toxins and its role in PCa progression has never been studied. We found that UPEC-secreted CNF1 promoted the migration and invasion of PCa cells and PCa metastasis. In vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…We first examined the effects of CNF1 on the migration and invasion abilities of bladder cancer cells. We purified and validated CNF1 and C866S (an inactive mutant of CNF1) recombinant proteins from UPEC strain as we previously described, 6 and treated bladder cancer cell lines 5637 and T24. The Transwell assay showed that wild‐type CNF1 markedly enhanced the migration and invasion of T24 and 5637 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first examined the effects of CNF1 on the migration and invasion abilities of bladder cancer cells. We purified and validated CNF1 and C866S (an inactive mutant of CNF1) recombinant proteins from UPEC strain as we previously described, 6 and treated bladder cancer cell lines 5637 and T24. The Transwell assay showed that wild‐type CNF1 markedly enhanced the migration and invasion of T24 and 5637 cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CNF1 promotes bacterial invasion into host cells by activating Rac 37 . Previously, we reported that CNF1 increased prostate cancer cell migration and invasion to promote prostate cancer metastasis through activating Cdc42, 6 and CNF1 reduced macrophage phagocytosis to induce inflammation during acute UTIs partially through Cdc42 38 . Schmidt reported that CNF1 enhanced breast cancer cell invasion through activating RhoC 39 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Functional studies demonstrate that PAK1 plays a significant role in cell proliferation, motility, apoptosis, and tumor progression (5). Phosphorylated-PAK1 (pho-PAK1) is overexpressed in several malignancies, including extra-mammary Paget's disease, breast, prostate, and squamous cell carcinomas (9)(10)(11)(12). These findings indicate a pivotal role of pho-PAK1 in tumor pathogenesis.…”
mentioning
confidence: 99%